Hukum Perceraian Disebabkan Suami Perantau (Analisa Terhadap Kasus Perceraian Di Kecamatan Hinai) - Ahmad Akbar; Muhammad Saleh (Peduli Riset dan Pengabdian Masyarakat, 2024)
Divorce is part of marriage, because there is no divorce without marriage first. In Islam, divorce is something that is not prohibited, but is an act that is hated by Allah SWT. In the society of Hinai District, divorce has occurred a lot, especially among migrant workers, so that a divorce that occurs among the community is no longer an unusual thing, because there are many factors that trigger divorce in the household. The aim of this research is to analyze divorce laws caused by migrant husbands in Hinai District. This research method uses qualitative research methods (field research). The primary data source was obtained through observation and interviews with the community and the parties concerned who had clear knowledge of the divorce case. Based on the results of research conducted by the author, the author concludes that the divorce law is due to the fact that according to Islam a middleman husband is obligatory if the husband is unable to fulfill his wife's rights and fulfill his obligations as a husband. And it is haram if it harms the husband. This is due to the low level of understanding and knowledge of husband and wife about the meaning of marriage or marriage. As well as the loss of the sanctity of marriage for husband and wife.